Seeing through the spin: The effect of news sentiment on firms' stock market performance - Stine Louise Daetz; Anna Kirstine Hvid; Alessandro Martinello; Rastin Matin (Danmarks Nationalbank, 2019)
The sentiment of news predicts the short-term stock market performance of individual companies. We find that this association is solely due to the idiosyncratic informational content of an article. We transparently quantify the association between news sentiment and stock market performance of S&P 500 companies, using articles written by Reuters between 2000 and 2018. First, we isolate the effect of sentiment independently of idiosyncratic informational content by exploiting a topicbased shift-share instrument. Second, we show that exogenous variation in article sentiment isolated through our topic-based shiftshare instrument, while strongly related to article sentiment, is unrelated to abnormal returns in the stock market.
Keywords: C55; D53; G15; G17; 330; Financial markets; Financial sector; Forecasting; Statistical method